PENATAAN ADMINISTRASI KELEMBAGAAN RT 14 DESA BRAJAN, TAMANTIRTO KASIHAN BANTUL - Mutmainah,, Nur Fitri; Mahendra, Gerry Katon (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2020)
This community service program is based on the fact that RT 14, Brajan, mostly consists of housing areas whose residents rent the houses. This situation creates difficulties in coordination and participants among the residents in various activities. That condition affects the comfort, discipline, cleanliness, and harmony among them. The method applied in this community service program is in the forms of coordination and deliberation towards the residents of RT 14. There are four activities conducted in this program: 1) strengthening organization by formulating job description to the boards of RT; 2) formulating rules and regulations in RT to motivate the residents’ active participations; 3) formulating resident database of RT 14; 4) creating empowering program for the residents. Hopefully, this community service program affects positive feedback to RT. 14 to be actively included in the development of Brajan, Tamantirto, Kasihan, Bantul.